2019
DOI: 10.1109/ted.2019.2896156
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Temperature-Dependent Substrate Loss in GaN-on-Si RF Technology

Abstract: Intrinsic limits to temperature-dependent substrate loss for GaN-on-Si technology, due to the change in resistivity of the substrate with temperature, are evaluated using an experimentally validated device simulation framework. Effect of room temperature substrate resistivity on temperaturedependent CPW line loss at various operating frequency bands are then presented. CPW lines for GaN-on-high resistivity Si are shown to have a pronounced temperature-dependence for temperatures above 150°C and have lower subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
(2 reference statements)
0
15
1
Order By: Relevance
“…On the other hand, Si substrates have worse electrical and thermal performance compared to SiC substrates, and the compromise performance versus cost must be evaluated at system/product level. Also, the choice between high-or low-resistivity substrates is source of debate and research [34]. Low-voltage GaN, although still at research level, is interesting for mobile user applications since it would bring some of the advantages of III-V technology but at a reduced cost compared to GaAs, mainly thanks to the possibility of integrating on a Si substrate.…”
Section: A Iii-v Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Si substrates have worse electrical and thermal performance compared to SiC substrates, and the compromise performance versus cost must be evaluated at system/product level. Also, the choice between high-or low-resistivity substrates is source of debate and research [34]. Low-voltage GaN, although still at research level, is interesting for mobile user applications since it would bring some of the advantages of III-V technology but at a reduced cost compared to GaAs, mainly thanks to the possibility of integrating on a Si substrate.…”
Section: A Iii-v Technologiesmentioning
confidence: 99%
“…A lower power (17 dBm), though on a wider bandwidth (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), is achieved in [17] on 130 nm SiGe BiCMOS. This two-stage differential PA features 10 dB gain and is compatible with satellite and ground-based communications and radar applications.…”
Section: A Standard Pasmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the use of high-resistivity substrates is necessary 2 , but also the achievement of both sufficient crystal quality and electrical resistivity of AlN/Si interface is required. Different phenomena have been reported as possible origins of parasitic conductivity and propagation losses: the diffusion of dopant species into the Si substrate 3 5 , the formation of an inversion layer at the AlN/Si interface 6 9 as well as degraded crystal quality 7 , 10 . In this context, the combination of several techniques is necessary to know the composition of the interface and its electrical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the RF substrate loss is a function of both the operating frequency and temperature. Chandrasekar et al recently quantitatively showed that the HR-Si substrate exhibits noticeable temperature dependence above 150 o C. Whereas, LR-Si substrate remains insensitive to temperature even at 200 o C. Furthermore, GaN-on-LR-silicon exhibits similar substrate loss as HR-Si for frequency < 12 GHz and therefore, could be a promising substrate for high power and high-frequency wireless communication applications in the S and X bands [3]. The realization of RF-GaN HEMTs on the LR-Si substrate has been already reported by several groups [4,5].…”
Section: Introductionmentioning
confidence: 99%